2021
DOI: 10.24321/2394.6539.202109
|View full text |Cite
|
Sign up to set email alerts
|

Understanding whether Air Filtration from Air Conditioners Reduces the Probability of Virus Transmission in the Environment

Abstract: As the COVID-19 global pandemic continues to remain severe, people tend to spend more time in an indoor dwelling and, much of the time in the summer, people choose to sit at air-conditioned homes, offices, or travel in air-conditioned vehicles. In order to reduce the occurrence of health-care-related diseases, cleaning and disinfecting of such environment is critical as polluted air posed threat to human wellbeing, reduces the life expectancy due to cardiovascular and respiratory diseases, including asthma and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The structure of COVID-19 virus is positive single strand RNA which shares genetically characteristics with SARS and Bat SARS corona viruses [2]. Every virus has a size of between 50 nm to 200 nm and comprises of some basic proteins like Spike, Envelop, Membrane and nucleocapsid which are represented by Alphabetical letters S, E, M and N respectively [3,4]. The virus envelop is created by utilizing the S, E and M proteins while as, N protein is responsible for holding the RNA genome of the virus [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of COVID-19 virus is positive single strand RNA which shares genetically characteristics with SARS and Bat SARS corona viruses [2]. Every virus has a size of between 50 nm to 200 nm and comprises of some basic proteins like Spike, Envelop, Membrane and nucleocapsid which are represented by Alphabetical letters S, E, M and N respectively [3,4]. The virus envelop is created by utilizing the S, E and M proteins while as, N protein is responsible for holding the RNA genome of the virus [3].…”
Section: Introductionmentioning
confidence: 99%
“…Every virus has a size of between 50 nm to 200 nm and comprises of some basic proteins like Spike, Envelop, Membrane and nucleocapsid which are represented by Alphabetical letters S, E, M and N respectively [3,4]. The virus envelop is created by utilizing the S, E and M proteins while as, N protein is responsible for holding the RNA genome of the virus [3]. As per the study conducted recently, it has been observed that bats serve as one of the prevalent natural hosts of virus [6], and intermediate host is Malayan Pangolin.…”
Section: Introductionmentioning
confidence: 99%
“…This virus is transmitted primarily through droplets caused by sneezing, coughing, speaking, singing, and inhalation. According to the published results, the aerosols containing SARS-CoV-2 were detected about 5 m away from an infected patient [ [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] ]. Besides, the effects of this virus on the environment over time are very destructive.…”
Section: Introductionmentioning
confidence: 99%
“…One study that tested the use of portable HEPA filtration units in a simulated COVID isolation room found that the volume treatment rates reached upwards of 20 air changes per hour, greater than the recommended 12, while capturing 98% of the surrogate aerosols . Others have shown that HEPA filters can significantly reduce the burden of airborne fungi, bacteria, and viruses, , including SARS-CoV-2 . Given the widespread availability of HEPA filters, particularly in the wake of the COVID-19 pandemic, it stands to reason that filter-based methods will continue to play a large role in future air purification.…”
Section: Introductionmentioning
confidence: 99%